The Sexual Strategy of the Son in Kafka: Terrorism and Exile: Сексуалната стратегија на синот кај Кафка: Тероризам и прогон - Koteska, Jasna; Tasev, Saše (Identities: Journal for Politics, Gender and Culture, 2001)
Author(s): Jasna Koteska | Јасна Котеска Title (English): The Sexual Strategy of the Son in Kafka: Terrorism and Exile Title (Macedonian): Сексуалноста на синот кај Кафка: Тероризам и прогон Translated by (English to Macedonian): Saše Tasev | Саше Тасев Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 67-81 Page Count: 14 Citation (English): Jasna Koteska, “The Sexual Strategy of the Son in Kafka: Terrorism and Exile,” Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001): 67-81. Citation (Macedonian): Јасна Котеска, „Сексуалната стратегија на синот кај Кафка: Тероризам и прогон“, превод од англиски Саше Тасев, Идентитети: списание за политика, род и култура, т. 1, бр. 1 (лето 2001): 67-81.